Kelas ke Publikasi: Pelatihan Penulisan Ilmiah Bagi Guru SMAN 12 Banjarmasin - Nur, Rahmat; Ruswinarsih, Sigit; Putra, Muhammad Aditya Hidayat; Widaty, Cucu; Reski P; Nadhita, Ramadhanti Salsabila; Ramadhani, Novia Eliza (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Improving teacher competence in writing scientific papers is a strategic step to support the improvement of professionalism and the quality of education in Indonesia. This is important because teachers not only act as educators, but also as innovators in producing new knowledge through their community service and scientific publications. This service focuses on a program to improve scientific writing designed to improve the scientific writing skills of teachers at SMAN 12 Banjarmasin. This program includes socialization, training, and intensive mentoring aimed at helping teachers understand the importance of writing scientific papers, improving writing skills, and publishing articles in accredited national journals. Based on the training activities, several main challenges faced by teachers were found, namely low motivation to write, limited technical skills, and financial constraints to attend training. This training program was attended by 21 teachers, where they received material on scientific writing techniques, the editing process, and the steps for submitting articles to journals. In addition, intensive mentoring was provided to ensure that teachers could complete the manuscript until it was ready to be published. The results of the program showed a significant increase in teachers' knowledge and motivation in writing scientific papers. Teachers were also able to document educational innovations based on evidence through quality articles. This program not only helps teachers improve their competence, but also contributes to efforts to improve the quality of education by expanding access to research-based information produced by teachers. Hopefully, this program can encourage a culture of scientific writing among educators.